Influence of soil structure interaction on the 4th story building - Kurniawandy Alex; Dayu Tiara Cindy; Aryanti Riza; Aminsyah Muhammad (E3S Web of Conferences)
Design structure generally is carried out using fixed-based restraints, which assume soil is infinitely rigid. The soil has a certain rigidity and can deform a structure commonly called soil structure interaction (SSI). However, practitioners rarely consider interaction between soil and structural systems because of their high complexity and long computing time. The SSI reviews need to be carried out to obtain a more accurate analysis according to original conditions in the soil. The study aims to identify structural behavior with consideration of SSI in a case study of the 4th-story building in Pekanbaru. Structural analysis is done linearly using response spectrum analysis and nonlinear pushover analysis. Modeling was made into two types: model 1 using fixed base and model 2 using spring located on the points along the pile foundation as a representation of SSI. The analysis results show the natural period increases by 20% in the X direction and 18% in Y. The base shear decreases by 18% in the X direction and 16% in Y. The maximum displacement increases by 29% in the X direction and 24% in Y. Nonlinear pushover analysis results in an increase in the performance point value of structure with SSI modeling.